Democratic Republic of the Congo Poverty and Social Impact Analysis : Mine Sector Reform - World Bank (Washington, DC, 2014)
Although the initial impetus for this poverty and social impact analysis (PSIA) was to inform the Gecamines retrenchment program, it quickly became evident during the scoping that the policy issues fell into two broad categories: a) Short term which involved the key issues of inquiry focusing on what the impact of this program might be, how to mitigate negative effects, and, according to the standard methodology for PSIA, whether the alternatives to restructuring were better or worse than the reform itself. Accordingly, a central question concerned the degree to which Gecamines' degradation had already caused adjustments in income and services and whether the alternative of not restructuring would have been preferable; and b) Medium term which stressed plans to restructure the sector included re-centering on the company's core activity and competency (ore extraction and production of copper and cobalt metal), and minimizing its role as a social service provider. The DRC Government had set a timetable of 2 years for this transfer, but viable options for the future provision of these services still had yet to be defined. Upstream work on the degree to which Gecamines' financial collapse has affected the provision of these ancillary services (and therefore the degree of impact from such a shift), as well as the design of mitigatory mechanisms and institutional options was essential as part of the PSIA.